2012
DOI: 10.4149/neo_2012_078
|View full text |Cite
|
Sign up to set email alerts
|

Total saponins of Tupistra chinensis induces apoptosis in A549 cells

Abstract: Tupistra chinensis Baker has been used as a folk remedy in China, and it has been shown to exhibit anti-inflammation, expectorant and anti-bacterial effects. In this study, we report the cytotoxic activity of the total saponins of Tupistra chinensis Baker (TST) against several carcinoma cell lines, including A549, MCF-7 and HeLa cells with the IC50 values of 4.11 μg/ml, 6.47 μg/ml and 7.78 μg/ml respectively. Treatment of A549 cells with TST resulted in growth inhibition and induction of apoptosis in a time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…On the other hand, our results showed that TPL increased the levels of pro-apoptotic proteins such as Fas and Bax, and decreased the level of anti-apoptotic protein Bcl-2. The cleavage of pro-Caspase-3 is a marker of the execution of apoptosis [17]. Our finding that TPL increased the level of cleaved Caspase-3 serves as additional evidence that TPL modulates the expression of apoptosis associated proteins to promote the apoptosis of prostate cancer cells.…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, our results showed that TPL increased the levels of pro-apoptotic proteins such as Fas and Bax, and decreased the level of anti-apoptotic protein Bcl-2. The cleavage of pro-Caspase-3 is a marker of the execution of apoptosis [17]. Our finding that TPL increased the level of cleaved Caspase-3 serves as additional evidence that TPL modulates the expression of apoptosis associated proteins to promote the apoptosis of prostate cancer cells.…”
Section: Discussionsupporting
confidence: 53%
“…7, Myricanol treatment significantly upregulated the mRNA expression level of Caspase-3, Caspase-9, Bax, and p21 and significantly downregulated the mRNA expression level of Bcl-2 in a dose-dependent manner. All gene expression changes contributed to cell apoptosis (Huang et al, 2012).…”
Section: Effects Of Myricanol On Mrna Expression Of Apoptotic Pathwaymentioning
confidence: 99%
“…The roots and rhizomes of T. c hinensis are commonly used as folk medicine to treat throat irritation, rheumatic diseases and snake-bites [2,3]. Modern pharmacological experiments have showed that the extracts of this species possess significant antitumor activities [4,5], moreover, two main kinds of components—cardenolides and saponins—were isolated from T. chinensis [3,6,7]. As part of our research project to find more diverse bioactive leading compounds from the medicinal herbs of the Qinba Mountains [8,9,10,11], the chemical constituents and pharmacological studies of T. chinensis were investigated, and two new furostanol saponins, 1β,2β,3β,4β,5β,26-hexahydroxyfurost-20(22),25(27)-dien-5,26- O -β- d -glucopyranoside ( 1 ), 1β,2β,3β,4β,5β,6β,7α,23ξ,26-nonahydroxyfurost-20(22),25(27)-dien-26- O -β- d -glucopyranoside ( 2 ), and a new spirostanol saponin (20 S ,22 R )-spirost-25(27)-en-1β,3β,5β-trihydroxy-1- O -β- d -xyloside ( 3 ) were obtained from the roots and rhizomes of T. chinensis together with the two known compounds tupisteroide B ( 4 ) and 5β-furost-Δ 25(27) -en-1β,2β,3β,4β,5β,7α,22ξ,26-octahydroxy-6-one-26- O -β- d -glucopyranoside ( 5 ) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%